Comparison of the Humphrey Field Analyzer and Photopic Negative Response of Focal Macular Electroretinograms in the Evaluation of the Relationship Between Macula Structure and Function - Hirooka, Kazuyuki; Yokoyama, Kenji; Tokumo, Kana; Kiuchi, Yoshiaki (Frontiers in Medicine, 2021)
Purpose: To investigate the association between macular inner retinal layer thickness and macula visual field (VF) mean sensitivity as measured by the Humphrey Field Analyzer (HFA) or macular function as measured by focal macular electroretinograms (ERGs) in patients with glaucoma. Methods: The participants in this cross-sectional study were 71 patients with glaucoma and 10 healthy controls. Macular inner retinal layer thickness and function were measured in all participants using optical coherence tomography (OCT) and HFA or focal macular ERGs, respectively. Macular OCT images were segmented into the macular retinal nerve fiber layer (mRNFL), macular ganglion cell layer/inner plexiform layer (GCL/IPL), and ganglion cell complex (GCC). Spearman correlation analysis was used to assess the relationship between macular inner retinal layer thickness and function. Results: Focal macular ERGs were composed of a negative wave (N1), a positive wave (P1), and a slow negative wave (N2). The N2 response density was significantly reduced in eyes with glaucoma, and was significantly associated with the thickness of the mRNFL (R = 0.317), GCL/IPL (R = 0.372), or GCC (R = 0.367). The observed structure–function relationship was also significantly correlated with the HFA VF mean sensitivity for each thickness (mRNFL [R = 0.728], GCL/IPL [R = 0.603], or GCC [R = 0.754]). Conclusions: Although a significant correlation was found between the N2 response density and the thickness of the macular inner layer, the observed structure–function relationship with the mean sensitivity of the HFA VF was higher than that of the N2 response density.